2021
DOI: 10.1103/physrevapplied.16.014040
|View full text |Cite
|
Sign up to set email alerts
|

Logic Gates Based on Synthetic Antiferromagnetic Bilayer Skyrmions

Abstract: Technologies based on magnetic skyrmions such as novel computational devices that can operate at high speed or low energy consumption have been proposed by many researchers.Recently, synthetic antiferromagnetic (SyAF) structures have been proposed to increase the stability and mobility of skyrmions by reducing or eliminating the skyrmion Hall effect. Here, we numerically study the current-induced dynamics of skyrmions on SyAF bilayer structures.We demonstrate the effective control and manipulation of SyAF skyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…The adders and logic gate operation are demonstrated using micromagnetic simulations performed on the GPU-accelerated open-source micromagnetic simulator software package MuMax3 [41], which have been used in simulating SyAF system as reported in Ref. [42][43][44][45].…”
Section: Model and Methodsmentioning
confidence: 99%
“…The adders and logic gate operation are demonstrated using micromagnetic simulations performed on the GPU-accelerated open-source micromagnetic simulator software package MuMax3 [41], which have been used in simulating SyAF system as reported in Ref. [42][43][44][45].…”
Section: Model and Methodsmentioning
confidence: 99%
“…magnetic skyrmions have also been proposed in recent years. [184,185,[188][189][190][191][192] Zhang et al were the first to propose a device with "Y"-shaped junction channels connecting inputs and outputs to control the duplication and merging of skyrmions and further constructed logic AND and OR gates. [188] Luo et al reported an architecture for reconfigurable skyrmion logic gates (Figure 12C) implementing SOT, SkHE, skyrmion-edge interactions, and skyrmion-skyrmion interactions.…”
Section: Other Applications: Logic and Magnonic Devicesmentioning
confidence: 99%
“…[185,189] Replacing ferromagnetic skyrmions and logic gates using AFSKs structures with better stability and mobility as information carriers were also designed. [190,191] Besides conventional binary computing, stochastic computing implemented by skyrmionic logic devices is also possible. [192] In addition, particlelike skyrmions with noncolinear spin nature and internal excitation modes contribute to future magnonic devices for manipulating spin waves.…”
Section: Other Applications: Logic and Magnonic Devicesmentioning
confidence: 99%
“…These textures appear promising for logic-inmemory applications since they intrinsically merge highdensity nonvolatile storage and logic capabilities. However, while a number of memory and logic concepts have been proposed based on skyrmions [1][2][3][4][5][6][7][8][9][10][11][12], several major issues have hindered their technological advancement. In a skyrmion racetrack [13], data is encoded through the distance between neighboring skyrmions and the memory operation relies on the synchronous shift of skyrmion trains, where the skyrmion interdistance remains constant.…”
Section: Introductionmentioning
confidence: 99%